Towards Learning a Knowledge Base of Actions from Experiential Microblogs - Kiciman, Emre (AAAI Spring Symposium on Knowledge Representation and Reasoning, 2015)
While today’s structured knowledge bases (e.g., Freebase) contain a sizable collection of information about entities, from celebrities and locations to concepts and common objects, there is a class of knowledge that has minimal coverage: actions. A large-scale knowledge base of actions would provide an opportunity for computing devices to aid and support people’s reasoning about their own actions and outcomes, leading to improved decision-making and goal achievement. In this short paper, we describe our first efforts towards building a distributional representation of actions and their outcomes, as learned from the timelines of individuals posting experiential microblogs.